Comparison of microphysical and topographical influences on warm season storm electrification between subtropical South America and Colorado - Gregg, Mitchell L., author; Rasmussen, Kristen L., advisor; Schumacher, Russ S., committee member; Chandrasekar, V., committee member; Morrison, Ryan, committee member (Colorado State University. Libraries, 2025)
Sixteen years of observations from the Tropical Rainfall Measurement Mission (TRMM) satellite's Precipitation Radar were key in identifying subtropical South America in the lee of the Andes as a global hotspot for convection, with frequent back-building over terrain producing intense convection yielding some of the highest lightning flash rates on Earth. These observations motivated the 2018 Remote sensing of Electrification, Lightning, And Mesoscale/microscale Processes with Adaptive Ground Observations (RELAMPAGO) field campaign, which sought to further investigate convection and electrification processes through the deployment of Colorado State University's CHIVO radar and a NASA Lightning Mapping Array (LMA). In 2021, the Preparatory Rockies Experiment for the Campaign in the Pacific ("PRE"-CIP) campaign took place in northern Colorado to study extreme precipitation and convection in the lee of the Rockies, deploying the same CHIVO radar near a permanent LMA network. CHIVO radar observations are used to identify discrete precipitation features and microphysical parameters key to storm electrification for approximately three months during the warm seasons in both Argentina and Colorado. LMA-observed lightning flashes are co-located with these precipitation features, allowing for analysis of the relationships between various microphysical parameters and lightning behavior throughout a storm's lifecycle, in both regions. The continuity in instrumentation, precipitation feature identification methods, and microphysical/hydrometeor identification calculations across both campaigns allows for the first direct comparison of microphysical drivers to electrification across a spectrum of storm modes between these two regions. Subtropical South America is characterized by systematically larger and taller convection with higher-altitude lightning flashes. LMA data from both campaigns demonstrates that lightning in Colorado occurs most frequently over the immediate plains east of the Rockies, while in South America, flashes occur more frequently over the foothills, highlighting the critical role of the Sierras de Córdoba, a secondary mountain range east of the Andes, in the back-building of convection observed in this region. Regressions developed between key microphysical parameters and lightning flash rates demonstrate that subtropical South American storms require significantly greater intense echoes and graupel volumes to produce similar lightning flash rates as storms in Colorado, suggesting a fundamental difference in electrification processes and the role of microphysical processes between these two regions. The fundamental differences in convective and lightning processes identified between these two regions demonstrates the need for future work to prioritize both microphysical and kinematic drivers in a more diverse sample of climate regions around the world.
Keywords: Colorado; lightning; radar; convection; Argentina; meteorology